Managing the Risk Communication in a Health Emergency, "The case of the eruption of the Calbuco Volcano", Chile 2015 - Díaz Bouquillard, Leonardo Javier (Revista Española de Comunicación en Salud, 2019)
The following work presents the communicational strategy developed by the Health Seremi institution, during the health emergency due to the eruption of the Calbuco Volcano (Los Lagos Region, Chile) in April 2015, to diminish the risks of health for people and communities exposed to the eruption. A preventive and informative strategy was reported through various resources, including website social networks, as well as institutional transparency in terms of information towards the community regarding air quality, water and ash presence. The analysis of institutional social networks (twitter) indicates that the sanitary discursive cores were properly fitting and spread in this social network.
Keywords: Public health; Risk communication; Health social network; Environmental monitoring; Epidemiological surveillance